Effects of acute alcohol consumption on emotion recognition in social alcohol drinkers. (March 2019) - Khouja, Jasmine N; Attwood, Angela S; Penton-Voak, Ian S; Munafò, Marcus R
Background: Research suggests that acute alcohol consumption alters recognition of emotional expressions. Extending this work, we investigated the effects of alcohol on recognition of six primary expressions of emotion. Methods: We conducted two studies using a 2 × 6 experimental design with a between-subjects factor of drink (alcohol, placebo) and a within-subjects factor of emotion (anger, disgust, sadness, surprise, happiness, fear). Study one ( n = 110) was followed by a direct replication study ( n = 192). Participants completed a six alternative forced choice emotion recognition task following consumption of 0.4 g/kg alcohol or placebo. Dependent variables were recognition accuracy (i.e. hits) and false alarms. Results: There was no clear evidence of differences in recognition accuracy between groups ( ps > .58). In study one, there were more false alarms for anger in the alcohol compared to placebo group ( n = 52 and 56, respectively; t (94.6) = 2.26, p = .024, d = .44) and fewer false alarms for happiness ( t (106) = –2.42, p = .017, d = –.47). However, no clear evidence for these effects was found in study two (alcohol group n = 96, placebo group n = 93, ps > .22). When the data were combined we observed weak evidence of an effect of alcohol on false alarms of anger ( t (295) = 2.25, p = .025, d = .26). Conclusions: These studies find weak support for biased anger perception following acute alcohol consumption in social consumers, which could have implications for alcohol-related aggression. Future research should investigate the robustness of this effect, particularly in individuals high in trait aggression.